Art nouveau plastic application in the architecture of Guatemala City - Cáceres Trujillo, Jorge Enrique (2021)
Art nouveau plastic expressions in architecture generated after the 1917 and 1918 earthquakes in Guatemala City, allow us to recognize the intrinsic meanings and their connotations. Reviewing the elements that influenced and led to implement these currents; this implies a review of the late nineteenth century until its development. Determining the momento in which they begin to manifest and their main characteristics is our objective. To do this, it is necessary to recognize and document various factors that interact in architecture. They are political, social, economic and cultural. By virtue of this, field visits, hemerographic, bibliographic and archive reviews were made, in order to string together details, data andelements that allow an articulated understanding of the architectural phenomenon. Art nouveau knowledge and expressions were recognized to have existed since the end of the 19th century, especially in texts or typographies; however, they had not been applied to architecture, but substantially until after the earthquakes. This situation, within several factors, will respond to a common socio-political phenomenon in Latin America: dictatorships. Within the documented expressions, be they floral or vegetal, anthropomorphic or zoomorphic, there is a prevalence of application around the openings; as well as on the floors. Likewise, there are explicit realities that connote a given intention, among them, marking thedate or time of this movement. In the end, this architecture came together in the first centenary of “Independence” (1921) and allows questioning its expressions and tendencies, evaluating changes or continuities as well to its conservation and management by 2021.